2023
DOI: 10.3390/plants12193492
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacins B, E and I Concentrations and Relationship with Drought Tolerance in Bottle Gourd [Lagenaria siceraria (Molina) Standl.]

Phumzile Mkhize,
Hussein Shimelis,
Jacob Mashilo

Abstract: Bottle gourd [Lagenaria siceraria (Molina) Standl.]) is a relatively drought-tolerant cucurbit due to the high composition of unique biochemical compositions, including cucurbitacin. The objective of this study was to determine the concentrations of cucurbitacins in bottle gourd and their relationship to drought tolerance. The study assessed 12 bottle gourd accessions grown under two moisture levels (i.e., non-stressed (NS) and drought-stressed (DS)) and three drought stress intensities (i.e., mild, moderate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
2
0
0
Order By: Relevance
“…It demonstrated that TCs can decrease oxidative stress and protect cell membranes from oxidative damage. This result is consistent with a previous study that CuB and CuE minimised cell damage caused by oxidative stress under drought-stressed environments ( Mkhize et al, 2023 ). Since the liver is the primary site of amino acid metabolism ( Ammar et al, 2022 ), CCl 4 injury leads to the disruption of amino acid metabolism.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It demonstrated that TCs can decrease oxidative stress and protect cell membranes from oxidative damage. This result is consistent with a previous study that CuB and CuE minimised cell damage caused by oxidative stress under drought-stressed environments ( Mkhize et al, 2023 ). Since the liver is the primary site of amino acid metabolism ( Ammar et al, 2022 ), CCl 4 injury leads to the disruption of amino acid metabolism.…”
Section: Discussionsupporting
confidence: 94%
“…The cold and drought environment upregulates genes related to cucurbitacin synthesis in H. pedunculosum , resulting in higher levels of CuB and its isomer compared to C. melo . This finding is consistent with literature showing cucurbitacin accumulation increases under drought stress ( Mkhize et al, 2023 ). Ultimately, growing in different climates impacts the plant biochemistry and results in divergence of therapeutic efficacy and safety between taxa ( Panossian, 2023 ), warranting further evaluation of understudied species like H. pedunculosum that may have unexplored benefits.…”
Section: Discussionsupporting
confidence: 94%